Multifunctional nanoagents for ultrasensitive imaging and photoactive killing of Gram-negative and Gram-positive bacteria - Jiali Tang; Binbin Chu; Jinhua Wang; Bin Song; Yuanyuan Su; Houyu Wang; Yao He (Nature Communications)
Abstract Simultaneous imaging and treatment of infections remains a major challenge, with most current approaches being effective against only one specific group of bacteria or not being useful for diagnosis. Here we develop multifunctional nanoagents that can potentially be used for imaging and treatment of infections caused by diverse bacterial pathogens. The nanoagents are made of fluorescent silicon nanoparticles (SiNPs) functionalized with a glucose polymer (e.g., poly[4-O-(α-D-glucopyranosyl)-D-glucopyranose]) and loaded with chlorin e6 (Ce6). They are rapidly internalized into Gram-negative and Gram-positive bacteria by a mechanism dependent on an ATP-binding cassette (ABC) transporter pathway. The nanoagents can be used for imaging bacteria by tracking the green fluorescence of SiNPs and the red fluorescence of Ce6, allowing in vivo detection of as few as 105 colony-forming units. The nanoagents exhibit in vivo photodynamic antibacterial efficiencies of 98% against Staphylococcus aureus and 96% against Pseudomonas aeruginosa under 660 nm irradiation.